On Particle Production in Lead-Gold Collision and Azimuthal Anisotropy at Top SPS Energy - Bao-Chun Li; Zhao Zhang (Advances in High Energy Physics, 2014)
In a multisource thermal model, we analyze the dependence of elliptic flow v2 on the transverse momentum PT. The model results are compared with the data of π-, KS0, p, and Λ measured in Pb + Au collisions at top SPS energy, 17.3 GeV. It is found that the azimuthal anisotropy in the evolution process of high-energy collisions is correlated highly to the number of participant nucleons.